Analisis Determinan Dana Pihak Ketiga Bank Umum Syariah di Indonesia - Ayif Fathur Rahman; Yuyun Setiawansi (Jurnal Ilmiah Ekonomi Islam, 2021)
This study aims to analyze the effect of inflation, exchange rate, BI Rate and Return On Assets (ROA) on Third Party Funds of Sharia Commercial Banks in Indonesia. Data used in the study are Third Party Funds, Inflation, Exchange Rate, BI Rate and Return On Assets (ROA). In this study using multiple linear regression methods and test classic assumptions with the help of Stata application. The results showed that Inflation variable (0,226) had a positive and not significant relationship to Third Part Funds of sharia commercial banks in Indonesia. BI Rate variable (0,000) has a negative and significant relationship to Third Part Funds of sharia commercial banks in Indonesia. While the Exchange Rate (0,000) and Return On Assets (0,000) have a positive and significant relationship to Third Part Funds of sharia commercial banks in Indonesia.